Early-Stage Defense Mechanism of the Cotton Aphid Aphis gossypii Against Infection With the Insect-Killing Fungus Beauveria bassiana JEF-544 - Im, Yeram; Park, So-Eun; Lee, Sue Yeon; Kim, Jong-Cheol; Kim, Jae Su (Frontiers in Immunology, 2022)
Aphis gossypii, commonly known as the cotton aphid, is a widely distributed pest of agricultural crops and acts as a vector for many serious plant viruses. Cotton aphid shows high resistance to chemical insecticides due to rapid rates of genetic diversity as a result of its short life cycle, seasonal migration, and host alteration. As an alternative, entomopathogenic fungi can be used to control cotton aphids in an environmentally sound manner. However, little is known about how cotton aphids respond to fungal infection. In this work, a new Beauveria bassiana strain JEF-554 (Bb JEF-544) was selected and isolated through bioassays with high virulence against cotton aphid. Early response of cotton aphid to Bb JEF-544 infection was analyzed at the transcriptome level. Infected aphids were collected two days after treatment at 25% lethal time (LT25), and total RNA of non-infected and Bb JEF-544-infected aphids was independently subjected to sequencing. Infected aphids showed significant up-regulation of the insect hormone biosynthesis pathway. Bursicon (Burs) and crustacean cardioactive peptide (CCAP) receptors involved in molting along with ecdysone synthesis were also strongly up-regulated in the aphid response to the fungal infection. In the cellular immune response, melanization in the hemocoel was significantly up-regulated, while phagocytosis was less actively transcribed. In conclusion, cotton aphids protect themselves from Bb JEF-544 infection by activating the cellular immune response including melanization and insect molting hormones to shed infected cuticles. In addition to describing the initial stages of Bb JEF-544 infection at the transcriptome level, this work provides potential treatment targets and insight into how fungal isolates can effectively be used to control this serious aphid species.